Legal structure and management of terminals: Focus on commercial issues and privatization - Orestis Schinas (Hamburg School of Business Administration (HSBA), 2010)
Most ports globally remain under public control, yet globalization and international logistic chains exercise pressure towards the dilution of the public control. This text presents briefly the institutional framework of ports and focuses on the operational and financial triggers to dilute public control. Then the key issues related to the market and the society are analyzed. This chapter concludes with a section on the bid process and the primal points discussed, negotiated and agreed in a concession procedure.
Keywords: 650; Port Management; Terminal Management; Privatization